2013
DOI: 10.1038/ncomms3081
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4-sulfoxide attenuates inflammatory cell infiltration and promotes cardiac wound healing

Abstract: The downstream consequences of inflammation in the adult mammalian heart are formation of a non-functional scar, pathological remodelling and heart failure. In zebrafish, hydrogen peroxide (H2O2) released from a wound is the initial instructive chemotactic cue for the infiltration of inflammatory cells, however, the identity of a subsequent resolution signal(s), to attenuate chronic inflammation, remains unknown. Here we reveal that Thymosin β4-Sulfoxide inhibits interferon-γ, and increases monocyte dispersal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…3,4 Recent studies revealed that Tβ4 increased cardiac function by promoting the survival of cardiomyocytes, [5][6][7] activating resident epicardial progenitor cells, 4,[8][9][10][11][12] and modulating inflammatory responses. 13 Being a peptide, Tβ4 has additional advantages over conventional growth factors because of its small size, high activity, and minimized immunogenicity, 14 and Tβ4 has been regarded as an attractive therapeutic agent for MI clinically (NCT00743769).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recent studies revealed that Tβ4 increased cardiac function by promoting the survival of cardiomyocytes, [5][6][7] activating resident epicardial progenitor cells, 4,[8][9][10][11][12] and modulating inflammatory responses. 13 Being a peptide, Tβ4 has additional advantages over conventional growth factors because of its small size, high activity, and minimized immunogenicity, 14 and Tβ4 has been regarded as an attractive therapeutic agent for MI clinically (NCT00743769).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the experimental data supports the thesis about the potential therapeutic properties of Tβ4 and derivatives of this peptide-sulfoxide and Ac-SDKP. These molecules are considered to be a potential factor applicable in the treatment of cardiovascular diseases, corneal and skin wounds and brain injuries [19,20,22,28]. Based on an understanding the numerous activities of Tβ4, it is postulated that the peptide will be used in the treatment of, inter alia, myocardial infarction, chronic heart failure, diabetes, lupus, stroke, multiple sclerosis, pressure ulcers, burns, dry eye, viral infections and septic shock [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that Tβ4 sulfoxide stimulates wound healing and reduced scarring in mice after myocardial infarction [41]. It is known that it inhibits neutrophil chemotaxis and interferon-γ antiviral activity, and causes the dissipation of monocytes, which prevents the formation of foci of chronic inflammation and allows proper wound healing without the formation of non-functional scars [41].…”
Section: Thymosin As a Factor Which Regulates Inhibition Of Scarringmentioning
confidence: 99%
See 1 more Smart Citation
“…When endogenous levels of TB4 are supplemented with exogenous delivery, animal models of cardiac injury show dramatic reduction in fibrosis,9, 10 increase in recruited stem cells,11, 12 and preservation of EF 10, 13. The underlying mechanism of TB4 cardioprotection has been attributed to increase in stem cell mobilization11, 12 and angiogenesis as well as reduction in inflammation and apoptosis 10, 14, 15. In cardiomyocyte culture, TB4 can prevent angiotensin II–induced hypertrophy,16 activate integrin‐linked kinase,10 and upregulate copper/zinc superoxide dismutase and catalase to provide resistance to oxidative stress 17…”
Section: Introductionmentioning
confidence: 99%